Effects of aromatherapy on fatigue, quality of sleep and quality of life in patients with inflammatory bowel disease: A feasibility study. (November 2022) - You, Lili; Guo, Na; Wang, Tiantian; Yu, Xiang; Kang, Xiaofeng; Guan, Yuxia; Liu, Hongpeng; Dong, Jing; Bian, Peili; Wang, Siyao; Bai, Chenxiao
Abstract: Background: Fatigue, poor sleep quality and poor quality of life (QoL) are recognised as common problems for patients with inflammatory bowel disease (IBD). This study aimed to evaluate feasibility and effect of aromatherapy on these problems in patients with IBD. Methods: Seventy IBD patients from a tertiary hospital in China were randomly assigned to an intervention group and a control group. During the 8-week intervention, the intervention group received aromatherapy through the skin and by inhalation, and the control group received routine nursing care. All patients were administered questionnaires at two sessions—the Multidimensional Fatigue Inventory, the Inflammatory Bowel Disease Questionnaire and the Pittsburgh Sleep Quality Index—before and after the intervention. The clinical trial registration number is ChiCTR2100045889. Results: Postintervention fatigue and sleep problems were relieved in the intervention group compared with the control group ( P  < 0.05). Moreover, QoL scores improved significantly in the intervention group ( P  < 0.05). Conclusion: These results suggested that aromatherapy may be an effective complementary treatment method to relieve fatigue and sleep problems and improve quality of life in IBD patients. Highlights: Aromatherapy is an effective complementary treatment to relieve fatigue and sleep problems and improve QoL in IBD patients. Aromatherapy is safe. Neither protocol deviations nor adverse events related to the use of aromatherapy occurred.